Two new species of the genus Psyllaphorura (Collembola: Onychiuridae) from the east of European Russia - Shveenkova, Yulia B.; Babenko, Anatoly B. (Zootaxa, 2021)
Two new species of the genus Psyllaphorura Bagnall, 1948, namely P. silvestris sp. nov. and P. pseudopodis sp. nov., are described from the European Russia. The former species can be compared to the Nearctic P. obesa (Mills, 1934) which has almost the same number of dorsal pseudocelli, but differs in having compound vesicles in PAO. Psyllaphorura pseudopodis sp. nov. is similar to P. altaica Weiner, Stebaeva & Kaprus’, 2019 recently described from the Altai Mountains, southern Siberia. Both these species have the same number and arrangement of the cephalic pseudocelli. Nonetheless, P. pseudopodis sp. nov. can be distinguished by the absence of pseudocelli on Abd. IV, only 2+2 dental setae and a shorter unguiculus. Besides this, P. pseudopodis sp. nov. is unique in the presence of a pair of ventral swellings on the fourth abdominal segment. Based on a revision of the types, P. sensillifera (Martynova, 1981) is considered a senior synonym of P. raoheensis Sun & Wu, 2013. Taxonomic notes on the most important diagnostic characters of the genus are given, as well as a key and a table summarizing these characters in all Psyllaphorura species known in the World so far.